PENGEMBANGANHANDOUTYANG DIAWALI PETA KONSEPADA MATERI SISTEM REPRODUKSI MANUSIA UNTUK MTsN - Silvianicha, Disa; Risdawati, M.Si., Renny; Susanti, Diana (Pendidikan Biologi, 2014)
ABSTRACT Handout is written form which prepared by the teacher for enrichment the knowledge of the students. Teaching material such a handout can be category as media of learning. Based on the observation and interview which have been conducted that in MTsN Lumpo class IX in 1 semester have never used a handout in learning process. They are only use the book that serve of the school and have limited quantity and also that book do not have a colour picture. The purpose of this reseach to resulted handout that begin with concept map in human reproduction  system  material which valid and practice. This reseach is development with use the development consists of 4-D models, that is define step, design step, develop step, and disseminate step, but in this reseach only in the develop step because of the limited the time and cost. The subject of this reseach consist of 4 validator, and two biology teachers for test practicalities and 24 student of MTsN Lumpo class IX in reproduction system material. The data of this reseach is a primary data that get from questionnaire and practicalities validity, then analysis with descriptive analysis. The result of this reseach have been got the validity by the lecturer and teacher  around 89,49% with valid criteria. The result of practicalities  test by the teacher and student get the average around  93,33% and92,27% with practice criteria. In conclusion that the teaching material  such handout that begin with concept map in human reproduction system material for MTsN was valid and very practice.